SCAPE: final best practice guidelines and recommendations - Ferreira, Miguel (2014)
The SCAPE project aims to enhance the state of the art in digital preservation with a particular emphasis on the scalability of its solutions: that is, their capacity to handle digital objects that may be very numerous, individually very large, heterogeneous or complex. The motivating force of the SCAPE project is scalability, interpreted in several dimensions: number of objects, size of objects, complexity of objects, and heterogeneity of collections. The best practice guidelines and recommendations cover three areas of digital preservation. These are: Large-scale long-term repository migration, Preservation of research data and Bit preservation.